2012
DOI: 10.1002/pros.22531
|View full text |Cite
|
Sign up to set email alerts
|

A high‐fat diet enhances proliferation of prostate cancer cells and activates MCP‐1/CCR2 signaling

Abstract: An HFD enhanced prostate cancer cell growth more strongly than an HCD or CD. MCP-1/CCR2 signaling may be involved in an HFD-induced prostate cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 36 publications
3
53
0
7
Order By: Relevance
“…At the end of the experiment (week 14), the mean tumor volume was significantly higher in the HFD group than in the LFD group (2569.9G 151.1 and 2010.3G120.7 mm 3 , respectively, PZ0.025; Fig. 2A), which was in accordance with the results of previous studies (Huang et al 2012). The amount of FA storage in tumors was found to be significantly higher in the HFD group than in the LFD group (172.2G43.9 and 119.6G17.8 nmol/mg, respectively, P!0.001; Fig.…”
Section: Increased Tumor Growth Fa Storage and Mic1 Expression In Lsupporting
confidence: 91%
“…At the end of the experiment (week 14), the mean tumor volume was significantly higher in the HFD group than in the LFD group (2569.9G 151.1 and 2010.3G120.7 mm 3 , respectively, PZ0.025; Fig. 2A), which was in accordance with the results of previous studies (Huang et al 2012). The amount of FA storage in tumors was found to be significantly higher in the HFD group than in the LFD group (172.2G43.9 and 119.6G17.8 nmol/mg, respectively, P!0.001; Fig.…”
Section: Increased Tumor Growth Fa Storage and Mic1 Expression In Lsupporting
confidence: 91%
“…Case-control and cohort studies have found positive associations between several cancers such as prostate cancer [67], ovarian cancer [68], breast cancer [69], colon cancer [70] etc, and an intake of foods with high levels of saturated fats, such as red meat, eggs, and dairy products. However, controversial results have also been reported about the role of high fat diet in carcinogenicity [71,72].…”
Section: Dietary Lipids and Cancermentioning
confidence: 99%
“…Recent studies have shown that high fat diet with saturated animal fat as major fat in the diet is associated with several cancer such as prostate cancer [67], colon cancer [80], ovarian cancer [68] and breast cancer [81] etc, whereas high fat diet with plant oils is not associated with cancer risk, however this may not be true, plant oils high in omega-6 fatty acids may be risk factors for cancer, which will be discussed in the polyunsaturated fatty acid section.…”
Section: Saturated Fatty Acidsmentioning
confidence: 99%
“…12 These rates are typically higher for Western nations [1], and 13 epidemiological studies have shown positive associations with 14 rates of obesity [2][3][4]. Diets with a high carbohydrate content 15 promote tumor progression in prostate cancer xenograft models 16 [5,6] We have also demonstrated the efficacy of a low carbohydrate 17 -high protein diet in attenuating growth of both murine squamous 18 cell and human colorectal carcinomas in mice [7]. More recently, 19 we reported effects of our low carbohydrate study diet tested alone 20 and in combination with celecoxib to significantly inhibit 21 metastases in both the 4T1 lung cancer model as well as prostate 22 cancer metastasis in the murine TRAMP mouse model [8].…”
Section: Introductionmentioning
confidence: 98%